Comparison of Whole Ovary Cryotreatments for Fertility Preservation - Lotz, Laura; Hauenstein, Tanja; Nichols-Burns, S. M.; Strissel, Pamela; Hoffmann, I.; Findeklee, S.; Dittrich, Ralf; Beckmann, Matthias; Oppelt, Patricia (Reproduction in Domestic Animals, 2015)
The goal of this study was to compare a traditional slow-freeze method (TF) with an open unidirectional slow freeze cooling system (UF) for whole ovary cryopreservation. Therefore, whole pig ovaries were randomly assigned to (A) fresh control, (B) traditional slow freeze (TF) or (C) unidirectional slow freeze (UF). Ovaries were perfused with 10% DMSO in Krebs-Ringer. For TF, whole ovaries were placed in specimen jars containing 10% DMSO and placed into a specialized container for freezing filled with propan-2-ol. For UF, whole ovaries were placed within a specially designed container containing 10% DMSO and transferred to a specialized freezing machine (CTE 920). Histological evaluation demonstrated intact morphology of follicles in all groups; however, an overall decrease of follicle numbers in TF (46%) and UF (50%) compared to fresh control. Live/dead assay indicated significantly lower populations of live cells in both TF (60%) and UF (58%) compared to fresh tissue (74%). TUNEL assay confirmed a difference in percentage of apoptotic follicles between fresh and TF, but there was no significant difference between fresh and UF. To improve the structural and functional integrity of whole ovaries, further investigation, especially into directional freezing, is needed. Whole ovary cryopreservation could provide opportunities for women facing fertility loss due to chemo- or radiotherapy treatment.
EVALuna2:17545